Arabidopsis and nicotiana anthocyanin production activated by maize regulators R and C1 - Lloyd, A.M. (Stanford University, Stanford, CA); Walbot, V; Davis, R.W (Science (American Association for the Advancement of Science), 1992)
Anthocyanin pathway-specific transcriptional activators Rand C1 from the monocot maize were expressed in two dicots, Arabidopsis thaliana and Nicotiana tabacum. Expression of R caused augmented anthocyanin pigmentation in both plant species and augmented trichome (hair) production in Arabidopsis. Alone, C1 had no effect. Hybrid transgenic Arabidopsis expressing both C1 and R produced anthocyanins in root, petal, and stamen tissues that normally never express anthocyanins. When R was expressed in the transparent testa glabrous (without anthocyanins and trichomes) mutant of Arabidopsis, the deficiency was complemented and both anthocyanins and trichomes were restored